Effects of continental anthropogenic sources on organic aerosols in the coastal atmosphere of East China - Shang, D. J.; Hu, M.; Guo, Q. F.; Zou, Q.; Zheng, J.; Guo, S. (Environmental PollutionEnvironmental PollutionEnvironmental Pollution, 2017)
Although organic compounds in marine atmospheric aerosols have significant effects on climate and marine ecosystems, they have rarely been studied, especially in the coastal regions of East China. To assess the origins of the organic aerosols in the East China coastal atmosphere, PM2.5 samples were collected from the atmospheres of the Yellow Sea, the East China Sea, and Changdao Island during the CAPTAIN (Campaign of Air PolluTion At INshore Areas of Eastern China) field campaign in the spring of 2011. The marine atmospheric aerosol samples that were collected were grouped based on the backward trajectories of their air masses. The organic carbon concentrations in the PM2,5 samples from the marine and Changdao Island atmospheres were 5.5 +/- 3.1 mu gC/m(3) and 6.9 +/- 2.4 mu gC/m(3), respectively, which is higher than in other coastal water atmospheres. The concentration of polycyclic aromatic hydrocarbons (PAHs) in the marine atmospheric PM2.5 samples was 17.0 +/- 20.2 ng/m(3), indicating significant continental anthropogenic influences. The influences of fossil fuels and biomass burning on the composition of organic aerosols in the coastal atmosphere of East China were found to be highly dependent on the origins of the air masses. Diesel combustion had a strong impact on air masses from the Yangtze River Delta (YRD), and gasoline emissions had a more significant impact on the "North China" marine atmospheric samples. The "Northeast China" marine atmospheric samples were most impacted by biomass burning. Coal combustion contributed significantly to the compositions of all of the atmospheric samples. The proportions of secondary compounds increased as samples aged in the marine atmosphere indicating that photochemical oxidation occured during transport. Our results quantified ecosystem effects on marine atmospheric aerosols and highlighted the uncertainties that arise when modeling marine atmospheric PM2.5 without considering high spatial resolution source data and meteorological parameters. (C) 2017 Published by Elsevier Ltd.
Keywords: air-pollution sources; anthropogenic sources; arctic-ocean; backward trajectory; Carbonaceous aerosol; coal combustion; coastal atmosphere; emissions; marine aerosol; pahs; particulate organic matter; rural site; secondary formation; tracers; yangtze-river delta